Silence and social suffering: an ethnographic study of adolescent sufferes of bullying - Lavín Cárcoba, José Ignacio (Revista de Antropología Social, 2022)
School bullying is a form of social suffering in the school environment. It affects the wellbeing of children and adolescents during their school years and can cause significant health problems in adulthood. As school bullying is not easily observed, it is typically shrouded in social silence. The aim of this ethnographic study is to expose the factors that contribute reproduction and production of school bullying. The ethnographic research was carried out in a secondary school and in an anti-bullying association between 2017 and 2019. The results exposed the role that the naturalisation of conflict in childhood and the silence of victimisation play in reproducing bullying in schools. The study concluded that the difficulty of recognising bullying and its visibility expose the moral distance between the adult world and the world of childhood and adolescent.
Keywords: bullying; ethnography; social suffering; moral orders; adolescents